2020
DOI: 10.1186/s41512-020-00084-1
|View full text |Cite
|
Sign up to set email alerts
|

Using machine-learning risk prediction models to triage the acuity of undifferentiated patients entering the emergency care system: a systematic review

Abstract: Background The primary objective of this review is to assess the accuracy of machine learning methods in their application of triaging the acuity of patients presenting in the Emergency Care System (ECS). The population are patients that have contacted the ambulance service or turned up at the Emergency Department. The index test is a machine-learning algorithm that aims to stratify the acuity of incoming patients at initial triage. This is in comparison to either an existing decision support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…Another publication about machine learning risk prediction models for triage of patients in the emergency department also considered 22/25 studies at high risk of bias. 33 A study assessing the performance of diagnostic deep learning algorithms for medical imaging reported 58 of 81 studies classified as overall high risk of bias. 7 Similar to our results, major deficiencies were found in the analysis domain including the number of events per variable, inclusion of enrolled participants in the analysis, reporting of relevant model performance measures, and overfitting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another publication about machine learning risk prediction models for triage of patients in the emergency department also considered 22/25 studies at high risk of bias. 33 A study assessing the performance of diagnostic deep learning algorithms for medical imaging reported 58 of 81 studies classified as overall high risk of bias. 7 Similar to our results, major deficiencies were found in the analysis domain including the number of events per variable, inclusion of enrolled participants in the analysis, reporting of relevant model performance measures, and overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…This study found deficiencies in how continuous variables and missing data were handled, and that model calibration was rarely reported. Another publication about machine learning risk prediction models for triage of patients in the emergency department also considered 22/25 studies at high risk of bias 33. A study assessing the performance of diagnostic deep learning algorithms for medical imaging reported 58 of 81 studies classified as overall high risk of bias 7.…”
Section: Discussionmentioning
confidence: 99%
“…Like the Emergency Severity Index, 31 some triage scores may achieve better performance in risk estimation but require some subjective variables. Some recent studies 32 , 33 , 34 highlighted the role of data-driven, objective clinical decision tools to help physicians rethink and reassess the triage process in the ED. Because our SERP scores only comprise objective elements, they can be easily computed by trained medical assistants or integrated into an existing hospital EHR, without the need for professional medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the other studies cited above, these authors included an external validation cohort; however, it is unclear whether their results can be generalized to Western countries. A recent systematic review [38], including 25 studies and 81 models, concluded that ML methods appear accurate in triaging undifferentiated patients entering the emergency care system. There was no clear benefit of using one technique over another; moreover, the majority of models' reporting did not give enough information on development, validation, and performance, which makes a critical appraisal difficult.…”
Section: Triage and Outcomes Predictionmentioning
confidence: 99%